O caso da assessoria de comunicação na Pastoral da Criança do bairro do Passo em São Borja - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The present work has as purpose to verify how the actions of the Communication Department contributed to the communication with the publics of Pastoral da Criança do Bairro do Passo. It was based on the methodology of the case study and the qualitative analysis, aiming to understand how the actions devised in the Strategic Planning of communication component were developed during the period of the Communication Department I and II. Aiming to highlight their positive and negative points. It should be noted that the actions were aimed at working on the image of Pastoral da Criança, communication among leaders, dissemination of actions in an efficient manner, aiming at ensuring the flow of information in an organized way, as well as maintaining a relationship between the institution, community and opinion-formers. Based on the communication advisory work, it was possible to conclude that the actions carried out during this period brought great benefits to the Pastoral da Criança, thus generating more visibility for the institution.
Keywords: Comunicação; Planejamento da comunicação; Conferência Nacional dos Bispos do Brasil. Pastoral da Criança; Trabalho voluntário; Communication planning; CNPQ::CIENCIAS SOCIAIS APLICADAS